Expression of Gls and Gls2 glutaminase isoforms in astrocytes - Cardona, Carolina; Sánchez-Mejías, Elisabeth; Dávila-Cansino, José Carlos; Martín-Rufián, Mercedes; Campos-Sandoval, José Ángel; Vitorica Ferrández, Javier; Alonso-Carrión, Francisco José; Mates-Sánchez, José Manuel; Segura-Checa, Juan Antonio; Norenberg, Michael; Rama Rao, Kakulavarapu; Jayakumar, Arumugan; et al. (Wiley, 2015)
The expression of glutaminase in glial cells has been a controversial issue and matter of debate for many years. Actually, glutaminase is essentially considered as a neuronal marker in brain. Astrocytes are endowed with efficient and high capacity transport systems to recapture synaptic glutamate which seems to be consistent with the absence of glutaminase in these glial cells. In this work, a comprehensive study was devised to elucidate expression of glutaminase in neuroglia and, more concretely, in astrocytes. Immunocytochemistry in rat and human brain tissues employing isoform-specific antibodies revealed expression of both Gls and Gls2 glutaminase isozymes in glutamatergic and GABAergic neuronal populations as well as in astrocytes. Nevertheless, there was a different subcellular distribution: Gls isoform was always present in mitochondria while Gls2 appeared in two different locations, mitochondria and nucleus. Confocal microscopy and double immunofluorescence labeling in cultured astrocytes confirmed the same pattern previously seen in brain tissue samples. Astrocytic glutaminase expression was also assessed at the mRNA level, real-time quantitative RT-PCR detected transcripts of four glutaminase isozymes but with marked differences on their absolute copy number: the predominance of Gls isoforms over Gls2 transcripts was remarkable (ratio of 144:1). Finally, we proved that astrocytic glutaminase proteins possess enzymatic activity by in situ activity staining: concrete populations of astrocytes were labeled in the cortex, cerebellum and hippocampus of rat brain demonstrating functional catalytic activity. These results are relevant for the stoichiometry of the Glu/Gln cycle at the tripartite synapse and suggest novel functions for these classical metabolic enzymes.
Keywords: Glutaminasa; Neuroglia; Glutaminase; Astrocytes; Glutamate; Glutamine; Glial cells; nucleus; Mitochondrion